Production of Terpenoids by Synthetic Biology Approaches - Zhang, Caizhe; Hong, Kui (Frontiers in Bioengineering and Biotechnology, 2020)
Terpenoids are a large family of natural products with remarkable diverse biological functions, and have a wide range of applications as pharmaceuticals, flavors, pigments, and biofuels. Synthetic biology is presenting possibilities for sustainable and efficient production of high value-added terpenoids in engineered microbial cell factories, using Escherichia coli and Saccharomyces cerevisiae which are identified as well-known industrial workhorses. They also provide a promising alternative to produce non-native terpenes on account of available genetic tools in metabolic engineering and genome editing. In this review, we summarize the recent development in terpenoids production by synthetic biology approaches.